Context-Responsive Anticoagulation Reduces Complications in Pediatric Extracorporeal Membrane Oxygenation - Lin, John C.; Barron, Lauren M.; Vogel, Adam M.; Colvin, Ryan M.; Baltagi, Sirine A.; Doctor, Allan; Gazit, Avihu Z.; Mehegan, Mary; O'Connor, Nicole; Said, Ahmed S.; Shepard, Mark; Wallendorf, Michael; et al. (Frontiers in Cardiovascular Medicine, 2021)
Purpose: We sought to determine the impact of a comprehensive, context-responsive anticoagulation and transfusion guideline on bleeding and thrombotic complication rates and blood product utilization during extracorporeal membrane oxygenation (ECMO). Design: Single center, observational pre- and post-implementation cohort study. Setting: Academic pediatric hospital. Patients: Patients in the PICU, CICU, and NICU receiving ECMO support. Interventions: Program-wide implementation of a context-responsive anticoagulation and transfusion guideline. Measurements: Pre-implementation subjects consisted of all patients receiving ECMO between January 1 and December 31, 2012 and underwent retrospective chart review. Post-implementation subjects consisted of all ECMO patients between September 1, 2013 and December 31, 2014 and underwent prospective data collection. Data collection included standard demographic and admission data, ECMO technical specifications, non-ECMO therapies, coagulation parameters, and blood product administration. A novel grading scale was used to define hemorrhagic complications (major, intermediate, and minor) and major thromboembolic complications. Main Results: Seventy-six ECMO patients were identified: 31 during the pre-implementation period and 45 in the post-implementation period. Overall observed mortality was 33% with no difference between groups. Compared to pre-implementation, the post-implementation group experienced fewer major hemorrhagic and major thrombotic complications, less severe hemorrhagic complications, and received less RBC transfusion volume per kg. Conclusions: Use of a context-responsive anticoagulation and transfusion guideline was associated with a reduction in hemorrhagic and thrombotic complications and reduced RBC transfusion requirements. Further evaluation of guideline content, compliance, performance, and sustainability is needed.